2020
DOI: 10.3390/ani10050766
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Concentrates Rich in Orange By-Products in Goat Feed and Its Effects on Physico-Chemical, Textural, Fatty Acids, Volatile Compounds and Sensory Characteristics of the Meat of Suckling Kids

Abstract: We analysed how replacing cereal concentrates with dehydrated orange pulp (DOP) in the diet of mother goats affects the meat quality of suckling kids. Three experimental diets for mother goats were designed. The DOP-0 diet contained commercial concentrates and alfalfa hay. In the DOP-40 and DOP-80 diets, 40% and 80% (respectively) of the cereal in the concentrate was replaced with pellets of DOP (the alfalfa hay component was unchanged). We evaluated the chemical composition, texture, water holding capacity, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…CM and TMR kids showed a similar content, and the values were three or four times higher than those of MG and MR kids. The values from MG and MR kids were similar to those indicated by other authors in the Payoya breed [ 50 ] and other Spanish goat breeds [ 1 ], as pointed out by the authors of [ 51 ] where intramuscular fat is around 2% in such young kids; however, the CM and TMR groups were well above this reference value. CM and TMR kids reached the slaughter weight earlier; that is, they presented higher growth rates than the other kids ( Table 2 ), which could indicate that they received milk with a higher energy content (maybe because of a higher quality of feed received by their dams).…”
Section: Resultssupporting
confidence: 88%
“…CM and TMR kids showed a similar content, and the values were three or four times higher than those of MG and MR kids. The values from MG and MR kids were similar to those indicated by other authors in the Payoya breed [ 50 ] and other Spanish goat breeds [ 1 ], as pointed out by the authors of [ 51 ] where intramuscular fat is around 2% in such young kids; however, the CM and TMR groups were well above this reference value. CM and TMR kids reached the slaughter weight earlier; that is, they presented higher growth rates than the other kids ( Table 2 ), which could indicate that they received milk with a higher energy content (maybe because of a higher quality of feed received by their dams).…”
Section: Resultssupporting
confidence: 88%
“…The total average dry matter (DM) intake per goat in the diet groups was 1.78, 1.76, and 1.75 kg/day in the C, DOP40, and DOP80 groups, respectively. For more details on animal management until early lactation, see Guzmán et al [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…This breed is a goat population traditionally reared under extensive or semi-extensive production systems, well-adapted to the low winter and high summer temperatures, and prevailing in the regions of southern Spain where they are most abundant [ 3 ]. As a result of this intensification, it is necessary to decrease livestock feeding costs by developing strategies, such as greater dependence on local feed resources, to increase the sustainability of livestock production systems [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the authors’ keywords revealed that VOC profiling of meat was mainly focused on two groups of meat products: one was muscle cuts, raw or cooked, obtained from different species and categories of meat animals, and the other was meat products obtained from industrial/artisanal processing. The first group mainly comprised meat cooked by different methods, such as grilling [ 69 ], frying [ 9 ], microwaving [ 70 ], boiling [ 71 ], etc. The second group mainly included fermented meat, ham, sausages (pork, horsemeat, poultry) [ 7 ], and burgers/patties (from different meats) [ 31 , 72 ].…”
Section: Resultsmentioning
confidence: 99%